Which is the Cause of Death?-A Case Report - Vijay Kumar Kaushik; M I Sheikh (Medsci Publications, 2017)
Homicide is one of the most serious consequences of interpersonal relation ending in violence. In all cases, where multiple fatal homicidal injuries have been inflicted, the principle cause of death may have to be determined. But in certain cases where marked degree of violence has been used, the autopsy facts emerge themselves with each injury playing a role in causing the death. It becomes one of the prime duties of a forensic expert to find out the cause of death in such cases, especially when multiple means of homicide are involved which indicate multiplicity of the assailants. Here is a case where the victim was murdered by inflicting multiple stab wounds over the chest and abdomen and was violently strangulated along with; all the injuries collectively contributed to the death in this case.Various factors and available literature are discussed here.